1989
DOI: 10.1128/jcm.27.10.2286-2294.1989
|View full text |Cite
|
Sign up to set email alerts
|

Typing of urogenital, maternal, and neonatal isolates of Haemophilus influenzae and Haemophilus parainfluenzae in correlation with clinical source of isolation and evidence for a genital specificity of H. influenzae biotype IV

Abstract: Over a period of 6 years, 114 strains of Haemophilus influenza and Haemophilus parainfluenzae were isolated from genital, mother-infant, or neonatal infections. Their serotypes, biotypes, antibiotic resistance phenotypes, and outer membrane protein (OMP) electrophoretic patterns were characterized and correlated with the various clinical outcomes. Genital H. influenza and H. parainfluenzae appeared to behave mostly as opportunistic pathogens; for instance, 62% of the cases of endometritis or pelvic inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 58 publications
2
45
0
2
Order By: Relevance
“…Carriage studies have shown that only 1.8/1000 parturient women carry non-encapsulated Hi in their genital tract [18], but they were found in 8/110 women with preterm rupture of membranes [19]. It has been suggested that unusually virulent NTHi biotype II or IV strains may preferentially cause invasive infections among neonates and pregnant women [19][20][21]. Further characterization of the strains in our study may therefore be of interest.…”
Section: Discussionmentioning
confidence: 80%
“…Carriage studies have shown that only 1.8/1000 parturient women carry non-encapsulated Hi in their genital tract [18], but they were found in 8/110 women with preterm rupture of membranes [19]. It has been suggested that unusually virulent NTHi biotype II or IV strains may preferentially cause invasive infections among neonates and pregnant women [19][20][21]. Further characterization of the strains in our study may therefore be of interest.…”
Section: Discussionmentioning
confidence: 80%
“…Genital, perinatal, and neonatal infections due to Haemophilus strains were first described in the early 1900s (5,14,27). The number of reported cases has increased in the last 20 years (7,13,14,22,28). Although specific tropism of some H. influenzae strains for the genital tract has been suggested on the basis of biotyping and serotyping studies (1,18,22,28), analysis of outer membrane protein patterns and genetic characterization of isolates do not support a general concept of specific genital strains.…”
Section: Discussionmentioning
confidence: 99%
“…The number of reported cases has increased in the last 20 years (7,13,14,22,28). Although specific tropism of some H. influenzae strains for the genital tract has been suggested on the basis of biotyping and serotyping studies (1,18,22,28), analysis of outer membrane protein patterns and genetic characterization of isolates do not support a general concept of specific genital strains. The exception is a very homogeneous group of genital strains, usually assigned to H. influenzae biotype IV, which share singular phenotypic and genotypic characteristics (15,17,19,20,21,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations